KEPEMIMPINAN TRANSAKSIONAL MEMBERIKAN PENGARUH PADA PELAYANAN PANGGILAN 112 MELALUI KUALITAS KEBIJAKAN SEBAGAI MODERASI - Marwiyah, Siti; Busthomi, Ach. Noor; Lailatul Fitria, Nurul Jannah (Universitas Panca Marga, 2023)
The government intervenes in a policy, especially in the public service sector. One of the government's interventions can be realized from the attitude of leadership in providing emergency services. Public services with emergency handling are needed by the community. For example, in Probolinggo City there is a call 112 Probolinggo City. In fact, this service is contained in the emergency call policy with NTPD 112 Probolinggo City. So the authors conducted in-depth research to find out and analyze the effect of transactional leadership on the quality of call 112 services in Probolinggo City and strengthened by the quality of emergency handling policies in Probolinggo City. This research applies quantitative research which is oriented towards theoretical variables by processing numbers followed by analysis. Collecting data with questionnaires, interviews, direct observation, and other documentation. The operational definition of variables in this research is the dependent variable, namely transactional leadership (X). The independent variable is service quality (Y). While the moderating variable is the quality of policy (Z). This research shows that transactional leadership has a direct, positive and significant influence on the quality of call 112 services in Probolinggo City. Coupled with the quality of the policy being able to moderate transactional leadership on the quality of call service 112 Probolinggo City. Kata kunci: policy; emergency; leadership; service; 112